Call to Arms: Don't Just Join, Get Involved - Bradley, Eric (Journal of environmental health, 2020)
Many young professionals entering the environmental health field want to build up their résumés quickly so it will stand out compared to others entering the field. One of the quickest ways to build up your résumé is by joining professional associations. Here, Bradley shares his over 20 years of experience in the environmental health field.